2019
DOI: 10.21070/2019/978-602-5914-71-3
|View full text |Cite
|
Sign up to set email alerts
|

Media Pembelajaran Inovatif

Abstract: Buku ini cenderung menekankan pada pemahaman konsep dan langkah aplikasi Media Pembelajaran Inovatif. Buku ini terdiri dari lima bab dengan penekanan yang berbeda-bede setiap babnya. Setiap bab juga telah disusun secara sitematis sesuai urutan materi dan tahapan pemahaman tentang Media pembelajaran Inovatif.Dalam membaca buku ini, para pembaca perlu membaca mulai dari bagian awal hingga akhir secara berurutan. Sebab sajian buku ini disusun berdasarkan urutan tahapan dan pemahaman secara teoritis dan praktis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
98

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 0 publications
1
45
0
98
Order By: Relevance
“…According to (Nurdyansyah, 2015) explaining that teaching materials are a guide for teachers in carrying out learning activities starting from activities and materials that will be delivered to students in learning while for students they will be used as guidelines for students to do individual learning in order to obtain information. According to a literature study found, learning to write poetry in grade IV has obstacles, especially in the teaching materials used, according to (M. Habibi et al, 2019, page 9) that teaching materials for writing poetry in schools do not provide appropriate strategies/techniques in the writing process.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Nurdyansyah, 2015) explaining that teaching materials are a guide for teachers in carrying out learning activities starting from activities and materials that will be delivered to students in learning while for students they will be used as guidelines for students to do individual learning in order to obtain information. According to a literature study found, learning to write poetry in grade IV has obstacles, especially in the teaching materials used, according to (M. Habibi et al, 2019, page 9) that teaching materials for writing poetry in schools do not provide appropriate strategies/techniques in the writing process.…”
Section: Introductionmentioning
confidence: 99%
“…Media pembelajaran juga merupakan inovasi terbaru dalam perkembangan Ilmu Pengetahuan dan Teknologi (IPTEK) di masa ini dalam membantu para pendidik untuk lebih kreatif dalam membuat media pembelajaran (Tafonao, 2018). Nurdyansyah (2019) menyatakan bahwa media pembelajaran ialah setiap alat yang dapat dimanfaatkan untuk menyampaikan materi pembelajaran yang dapat meningkatkan perhatian, minat, pikiran dan perasaan siswa untuk mencapai tujuan pembelajaran.…”
Section: Pendahuluanunclassified
“…Hasnul Fikri Mengungkapkan media bisa tertuju pada sesuatu yang meneruskan ataupun mengantar informasi (pesan) antar penerima pesan dan sumber (pemberi pesan), media pembelajaran sebagai faktor yang bisa memberi motivasi siswa agar meraih hasil belajar yang terbaik serta memotivasi siswa dalam melakukan pembelajaran (Hasnul Fikri, 2018). Media pembelajaran termasuk komponen pembelajaran yang memainkan peran vital untuk kegiatan belajar mengajar (Nurdyansyah, 2019). pada aktivitas belajar mengajar penggunaan media pembelajaran bisa menumbuhkan minat dan keinginan yang baru, memberi pengaruh psikologi kepada siswa, dan bahkan menumbuhkan rangsangan dan motivasi aktivitas belajar (Yuniastuti, Miftakhuddin, 2021).…”
Section: A Pendahuluanunclassified